Transformasi Digital untuk Praktik Berkelanjutan dalam Bidang Digital Finance, Blockchain dan Cryptocurrencies, dan E-Goverment - Kurniawati, Yulia Ery; Halim, Erwin; Mailangkay, Adele BL; Syamsuar, Dedy (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
Digital transformation is developing rapidly and has become a global trend. It encourages sustainable practices in various sectors. These sectors include digital finance, blockchain and cryptocurrency, and e-Government. This Community Service (PkM) is three sessions from the NUNI IT Online Seminar Phase 6 with the topic "Digital Transformation for Sustainable Practices" organized by the Nationwide University Network in Indonesia (NUNI) and held on 27 May - 7 June 2024. This PkM explains three materials about research in digital finance, understanding blockchain and cryptocurrencies in the digital economy, and challenges and obstacles in e-government in Indonesia. The third session was held on 28-30 May 2024. The results of this activity were the transfer of knowledge and the addition of participants' insight and knowledge about the topics presented.